Reference intervals for plasma free metanephrines with an age adjustment for normetanephrine for optimized laboratory testing of phaeochromocytoma. (January 2013) - Eisenhofer, Graeme; Lattke, Peter; Herberg, Maria; Siegert, Gabriele; Qin, Nan; Därr, Roland; Hoyer, Jana; Villringer, Arno; Prejbisz, Aleksander; Januszewicz, Andrzej; Remaley, Alan; Martucci, Victoria; et al.
Background: Measurements of plasma normetanephrine and metanephrine provide a useful diagnostic test for phaeochro-mocytoma, but this depends on appropriate reference intervals. Upper cut-offs set too high compromise diagnostic sensitivity, whereas set too low, false-positives are a problem. This study aimed to establish optimal reference intervals for plasma normetanephrine and metanephrine. Methods: Blood samples were collected in the supine position from 1226 subjects, aged 5-84 y, including 116 children, 575 normotensive and hypertensive adults and 535 patients in whom phaeochromocytoma was ruled out. Reference intervals were examined according to age and gender. Various models were examined to optimize upper cut-offs according to estimates of diagnostic sensitivity and specificity in a separate validation group of 3888 patients tested for phaeochromocytoma, including 558 with confirmed disease. Results: Plasma metanephrine, but not normetanephrine, was higher (P < 0.001) in men than in women, but reference intervals did not differ. Age showed a positive relationship (P < 0.0001) with plasma normetanephrine and a weaker relationship (P = 0.021) with metanephrine. Upper cut-offs of reference intervals for normetanephrine increased from 0.47 nmol/L in children to 1.05 nmol/L in subjects over 60 y. A curvilinear model for age-adjusted compared with fixed upper cut-offs for normetanephrine, together with a higher cut-off for metanephrine (0.45 versus 0.32 nmol/L), resulted in a substantial gain in diagnostic specificity from 88.3% to 96.0% with minimal loss in diagnostic sensitivity from 93.9% to 93.6%. Conclusions: These data establish age-adjusted cut-offs of reference intervals for plasma normetanephrine and optimized cut-offs for metanephrine useful for minimizing false-positive results.